Do Law Clinics Need Trigger Warnings? Philosophical, Pedagogical and Practical Concerns - Kate Seear (Legal Education Review)
In recent years, there has been growing concern about poor mental health and wellbeing of both law students and those in the profession. These concerns have been building for the last two to three decades, and have gathered pace in the last few. As concerns about the impact of lawyering on those in the profession have grown, a separate but related set of developments have been unfolding across universities. Universities all over the world have been developing a heightened awareness of student needs, sensitivities and mental health, and have been considering how teaching methods, materials and styles may impact these. As part of this, a number of North American universities have begun to grapple with the question of whether content to which students are exposed in their degree should contain a ‘trigger warning’. A trigger warning is a cautionary note designed to alert students to potentially sensitive material in a syllabus, and which may, in some circumstances, allow them to be exempted from course content. Trigger warnings have generated significant debate in the United States academy. In other parts of the world, such as Australia, these debates are also gathering pace, with the appropriateness of trigger warnings for clinical legal education now also being considered. This paper explores whether trigger warnings are necessary in clinical legal education. This paper unfolds in three parts. First, drawing upon theoretical concerns about the politics of emotion, including ideas from Sara Ahmed and Judith Butler, I consider the philosophical and conceptual aspects of trigger warnings, including the dangers of academics defining which content is ‘triggering’ and which is not. Second, I explore some of the pedagogical implications that would flow from the use of trigger warnings in law clinics. Third, I examine some of the practical implications of the deployment of trigger warnings in clinics. I argue that academics should be cautious about calls to impose trigger warnings in clinical legal education, because they introduce a series of major philosophical, practical and pedagogical problems. I also argue that although trigger warnings may appear, on the face of it, to align with the values that many clinicians would see as being at the heart of clinical legal education, including social justice, respect for clients, minorities and disadvantaged populations, trigger warnings have the potential to paradoxically instantiate power dynamics, to entrench injustice, and to foreclose intellectual curiosity. They also have a series of implications for the ethics and politics of legal practice, some of which I consider to be both substantial and antithetical to the proper practice of clinical legal education.